Ocular Color-Coded Sonography – A Promising Tool for Neurologists and Intensive Care Physicians - Ertl, M.; Barinka, F.; Torka, E.; Altmann, M.; Pfister, K.; Helbig, H.; Bogdahn, U.; Gamulescu, M. A.; Schlachetzki, F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Ocular color-coded duplex sonography (OCCS), when performed within the safety limits of diagnostic ultrasonography, is an easy noninvasive technique with high potential for diagnosis and therapy in diseases with raised intracranial pressure and vascular diseases affecting the eye. Despite the capabilities of modern ultrasound systems and its scientific validation, OCCS has not gained widespread use in neurological practice. In this review, the authors describe the technique and main parameter settings of OCCS systems to reduce potential risks as thermal or cavitational effects for sensitive orbital structures. Applications of OCCS are the determination of intracranial pressure in emergency medicine, and follow-up evaluations of idiopathic intracranial hypertension and ventricular shunting by measuring the optic nerve sheath diameter. A diameter of 5.7 – 6.0 mm corresponds well with symptomatically increased intracranial pressure (> 20 cmH2O). OCCS also helps to discriminate between different etiologies of central retinal artery occlusion – by visualization of a “spot sign” and Doppler flow analysis of the central retinal artery – and aids the differential diagnosis of papilledema. At the end perspectives are illustrated that combine established ultrasound methods such as transcranial color-coded sonography with OCCS.
Keywords: CNS; eye; ultrasound color Doppler; intracranial hypertension; emergency medicine